2017
DOI: 10.1136/acupmed-2016-011228
|View full text |Cite
|
Sign up to set email alerts
|

Influence of de qi on the immediate analgesic effect of SP6 acupuncture in patients with primary dysmenorrhoea and cold and dampness stagnation: A multicentre randomised controlled trial

Abstract: Objective The aim of this multicentre randomised controlled trial was to investigate the contribution of de qi to the immediate analgesic effect of acupuncture in patients with primary dysmenorrhoea and the specific traditional Chinese medicine diagnosis cold and dampness stagnation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 15 publications
0
22
0
3
Order By: Relevance
“…"Deqi" is a needle response describing how the patients feel when they receive the needle insertion, which is regarded as a uniquely key predictor and an essential role in therapeutic effectiveness of acupuncture for stroke recovery [23]. Until now, there isn't a standard needle sensation assessment scale but all the self-designed scales consist of two parts.…”
Section: Needle Sensation Assessment Scale (Nsas)mentioning
confidence: 99%
“…"Deqi" is a needle response describing how the patients feel when they receive the needle insertion, which is regarded as a uniquely key predictor and an essential role in therapeutic effectiveness of acupuncture for stroke recovery [23]. Until now, there isn't a standard needle sensation assessment scale but all the self-designed scales consist of two parts.…”
Section: Needle Sensation Assessment Scale (Nsas)mentioning
confidence: 99%
“…The cognitively induced somatosensation observed in our study corroborates studies that have reported remarkably similar de qi sensation between verum and sham acupuncture with regard to intensity, quality, and somatotopic pattern ( Beissner et al, 2015 ; Lee et al, 2014 ; Salih et al, 2010 ). De qi sensation, the somatosensation elicited by acupuncture stimulation, has been asserted to be a useful predictor of successful acupuncture treatment ( Spaeth et al, 2013 ; Zhao et al, 2017 ). Furthermore, cognitive factors in acupuncture stimulation, such as a patient's perception and expectations, can influence acupuncture analgesia ( Vase et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Deqi is a needle response describing how the patients feel when they receive the needle insertion, which is regarded as a unique key predictor and an essential role in the therapeutic effectiveness of acupuncture for stroke recovery. 31 The self-designed NSAS we adopt has been tested in our previous studies, 32 which includes Deqi features (sourness, numbness, tingling, aching and propagated feeling along the meridians) and rating of Deqi. Patients will describe the intensity of needle sensation by Visual Analogue Scale (0 stands for none, 10 stands for unbearable).…”
Section: Needle Sensation Assessmentmentioning
confidence: 99%